EVALUASI PROGRAM SIDOARJO MATERNAL DAN NEONATAL EMERGENCY SMS GATEAWAY (SI MANEIS) DI RSUD KABUPATEN SIDOARJO - Sindika Ayu Tristiara Gani; Tjitjik Rahaju (Universitas Negeri Surabaya, 2022)
The Sidoarjo Maternal and Neonatal Emergency SMS Gateway program is a new breakthrough initiated by the Sidoarjo District Hospital in 2013 and began to be implemented in 2015 based on the Decree of the Director of the Sidoarjo Regional General Hospital Number: 188/253/404.6.8/2015 about Sidoarjo Maternal and Neonatal Emergency SMS Gateway Services. In order to improve the effectiveness and efficiency of the maternal and neonatal referral system at the Sidoarjo District Hospital, which previously did not run optimally so that it had an impact on maternal and infant mortality. This study aims to identify and describe the results of the evaluation of the Si MaNEeis program at the Sidoarjo District Hospital using the William N. Dunn evaluation theory which includes six indicators, namely effectiveness, efficiency, adequacy, leveling, responsiveness, and accuracy. The type of research used is descriptive with a qualitative approach. Data collection techniques through interviews, observation, and documentation. The results showed that the implementation of the Si MaNEis program at the Sidoarjo District Hospital had run quite well and met the six policy evaluation indicators although there were some shortcomings. Suggestions for the implementation of the Si MaNEis program are the development of applications that can be downloaded via the Android and iOS systems, simplification of the referral system needs to be done to make it easier for the referrer to fill in patient data, socialization and technical guidance are further improved regularly and thoroughly.